Exercise-based telerehabilitation in chronic low back pain – a scoping review - Jenny Sivertsson; Ninni Sernert; Kristina Åhlund (BMC Musculoskeletal Disorders)
Abstract Background Low back pain is a major global health problem. Physiotherapy involving exercises is considered first-line treatment. In recent years digital tools including telerehabilitation have increased, but the interventions are diverse. The aim of this study was to map how telerehabilitation approaches are used in studies evaluating exercise-based rehabilitation in patients with chronic low back pain. Methods A systematic literature search was conducted in PubMed, Cinahl and Cochrane Central between January 2017 and January 2024 for original studies on adults, 18 years or older, with chronic low back pain who received exercise-based telerehabilitation. Results The database search resulted in 1019 articles. Out of 37 full texts that were screened 28 articles were included in the analysis. The included studies showed a wide variation regarding technological solutions, interventions and outcome measures. The exercise-based telerehabilitation was usually delivered asynchronously via a smartphone application. The most common clinical outcome measure was pain and disability/physical function. Telerehabilitation compared to conventional exercise therapy showed similar clinical improvements. Conclusions This scoping review confirms the heterogeneity within this research area but also contributes by mapping and demonstrating some knowledge gaps in the literature. Further research focusing on synchronous and group interventions are needed. The new technologies described in the included studies provide added value through functional improvements and task redesign. Trial registration OSF https//doi.org/10.17605/OSF.IO/EMKCG.